1999
DOI: 10.1002/(sici)1099-0518(19990715)37:14<2355::aid-pola9>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinkable polymers for optical waveguide devices. II. Fluorinated ether ketone oligomers bearing ethynyl group at the chain end

Abstract: Fluorinated ether ketone oligomers bearing a crosslinkable ethynyl group at the chain end have been investigated for low-loss polymer optical waveguide devices. These oligomers are designed to achieve low birefringence and were synthesized by the reaction of 4,4Ј-(hexafluoroisopropylidene)diphenol with an excess decafluorobenzophenone, followed by reaction with (phenylethynyl)phenol or ethynylphenol. The molecular weights (M n s) and polydispersities of the oligomers determined by GPC with polystyrene standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 0 publications
4
47
0
Order By: Relevance
“…Here, p ϭ1Ϫ 1 , with 1 the monomer 1 volume fraction. The number of segments of the monomer and the polymer molecules are given by 1 and p , respectively. Here, a segment is a volume unit that corresponds to the smallest monomer unit in the system, and should not be confused with a monomer unit in general in a system that contains monomers of different sizes.…”
Section: One Monomermentioning
confidence: 99%
See 2 more Smart Citations
“…Here, p ϭ1Ϫ 1 , with 1 the monomer 1 volume fraction. The number of segments of the monomer and the polymer molecules are given by 1 and p , respectively. Here, a segment is a volume unit that corresponds to the smallest monomer unit in the system, and should not be confused with a monomer unit in general in a system that contains monomers of different sizes.…”
Section: One Monomermentioning
confidence: 99%
“…Following again the Flory-Huggins theory, the chemical potential 1 illum of monomer 1 is given by the following expressions: 9…”
Section: Two Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Planar waveguide technology, in particular, is being researched as a solution to the traffic jam from long haul, oversea delivery of information to the short, metropolitan connection. 53 Polymers including polyacrylates, 54,55 polyimides, 56,57 polyethers, 58,59 and polysiloxanes 60,61 fill this requirement over inorganic counterparts because of their well-known optical properties, ease of processing, cost effectiveness, flexibility, toughness, tunability, and long term stability. However, in such systems CÀ ÀH vibration becomes the most significant role of attenuation in the near infrared (NIR) region.…”
Section: Applications Photonicsmentioning
confidence: 99%
“…3,17 In previous research, we synthesized a series of fluorinated poly(phthalazinone ether)s 18 and a crosslinked poly(phthalazinone ether ketone) bearing tetrafluorostyrene groups. 19 We previously demonstrated that fluorinated poly(phthalazinone ether)s had inherently low optical losses and good refractive index controllability, whereas the crosslinked poly (phthalazinone ether ketone) had low birefringence and good adhesion with semiconductor substrates.…”
Section: Introductionmentioning
confidence: 99%